Gene expression profile during seed development of Bixa orellana accessions varying in bixin pigment - Cárdenas-Conejo, Yair; Narváez-Zapata, José Alberto; Carballo-Uicab, Víctor Manuel; Aguilar-Espinosa, Margarita; Us-Camas, Rosa; Escobar-Turriza, Pedro; Comai, Luca; Rivera-Madrid, Renata (Frontiers in Plant Science, 2023)
Diverse morphological, cellular and physiological changes occur during seed maturation in Bixa orellana, when the seed tissues form specialized cell glands producing reddish latex with high bixin amounts. Transcriptomic profiling during seed development in three B. orellana accessions with contrasting morphologic characteristics showed enrichment in pathways of triterpenes, sesquiterpenes, and cuticular wax biosynthesis. Analysis of key genes of the mevalonate (MVA) and of the 2C-methyl-D-erythritol-4-phosphate (MEP) pathways revealed specific activity of orthologues of BoHMGR, BoFFP, BoDXS, and BoHDR. This suggested that isoprenoid production is necessary for compounds in the reddish latex of developing seeds. The carotene-related genes BoPSY2, BoPDS1 and BoZDS displayed high correlation with bixin production, consistently with the requirement for carotene precursors for apocarotenoid biosynthesis. Some BoCCD gene members (BoCCD1-4, BoCCD4-1, BoCCD4-3 and BoCCD4-4), some BoALDH gene members (BoALDH3I1, BoALDH2B4 and BoALDH3H1-1) and some BoMET gene members (BoSABATH3 and BoSABATH5) were highly correlated to bixin in the final seed development stage. This suggested a contributing role for several genes in apocarotenoid production. The results revealed high genetic complexity in the biosynthesis of reddish latex and bixin in specialized seed cell glands in different accessions of B. orellana suggesting a gene expression coordination between both metabolite biosynthesis processes.